Cohesion and Metaphor Aspects in Andabhuana Text - Mahardika, Ida Bagus; Weda Kusuma, I Nyoman; Mulyono, I Nyoman; Rai Putra, Ida Bagus (e-Journal of Linguistics; Vol.7. Januari 2013 No. 1, 2013)
Cohesion and metaphor are the unique and interesting parts of language aspects in Andhabhuan text to research. They are quite dominant aspects in the story in developing its literature aesthetic. This research is based on the arts technical and analytical method. The result of the research on those two aspects shows that traditional aesthetic style in arts, as described in Andabhuana verses emphasize on the reference, meaning, selection and variation of words. The language parts used are aimed at bringing the text ideology to humanity perspective, especially the ?iwatattwa values as parts of Hindu teaching. Hence the cohesion and metaphor in Andabhuana text  are  semiotic description to transform to Balinese Hindus as most of them follow ?iwatattwa belief.
Keywords: cohesion and metafor